Three Student Engagement Strategies to Help Elementary Teachers Work Smarter, Not Harder, in Mathematics. (April 2018) - Hirsch, Shanna E.; Ennis, Robin Parks; Driver, Melissa K.
Many students with and/or at risk for emotional and behavioral disorders have academic deficits that affect their performance in mathematics. In addition, these students' behavioral issues may interfere with their academic achievement. For these students, it makes sense for teachers to consider implementing research- and/or evidence-based practices that simultaneously promote mathematics fluency and increased academic engagement. The purpose of this article is to provide teachers with three instructional practices that we believe can easily be integrated into mathematics instruction. The practices are opportunities to respond, token economy, and self-monitoring.